2014
DOI: 10.1021/nl500682j
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure and Dynamics of Metal Dopant Pairs in Graphene

Abstract: We present an atomic resolution structural study of covalently bonded dopant pairs in the lattice of monolayer graphene. Two iron (Fe) metal atoms that are covalently bonded within the graphene lattice are observed and their interaction with each other is investigated. The two metal atom dopants can form small paired clusters of varied geometry within graphene vacancy defects. The two Fe atoms are created within a 10 nm diameter predefined location in graphene by manipulating a focused electron beam (80 kV) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
172
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(174 citation statements)
references
References 36 publications
2
172
0
Order By: Relevance
“…Nevertheless, the major source of the magnetism in two systems is quite different. These fascinating phenomenon, in combination with the fact that the substitutional 2D materials has been artificially synthesis by many groups [47][48][49][50][51][52][53], can paves a new route at nanoscale for novel functionalities of optical and spintronics devices.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the major source of the magnetism in two systems is quite different. These fascinating phenomenon, in combination with the fact that the substitutional 2D materials has been artificially synthesis by many groups [47][48][49][50][51][52][53], can paves a new route at nanoscale for novel functionalities of optical and spintronics devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, no such materials have been synthesised for CO 2 reduction as synthesis of single atom catalysts is often quite difficult and requires appropriate support structures for the particular application. [60][61][62] For Type I materials, trace levels of metal nanoparticles have shown to significantly enhance the CO 2 RR activity of graphene [23] and recent studies have also extended this to N-graphene. [63,64] Monodisperse Cu NPs supported by pyridinic-N graphene (p-NG) and were found to be selective for CO 2 reduction to ethylene.…”
Section: Graphene Supported Nanoparticlesmentioning
confidence: 99%
“…[108] Further, these materials maximise metal utilisation and can greatly improve catalytic efficiency. [109,110] Motivated by the work of He et al, [60] DFT studies were extended to investigate transition metal dopant pairs (dimers) on graphene supports in order to reveal whether these dispersed metal centres can be tuned to CO 2 RR. [107] The computational hydrogen electrode (CHE) was utilised to elucidate free energy profiles, electrocatalytic performance and reaction pathways and it was found that dimer geometry and configuration on the graphene support plays a very important role in the adsorption of intermediate species.…”
Section: Nanostructured Carbon Supportsmentioning
confidence: 99%
“…The question of whether dispersed atomic sites can be tuned to reductive conversion of CO 2 using a different supporting material then arises. Here, inspired by the successful fabrication of graphene-supported Fe dopant pairs, 28 we systematically investigate CO 2 electroreduction on various graphene-supported first-row transition metal dopant pairs. The adjacent graphene single vacancy supported Cu 2 , MnCu, and NiCu pair dopants are identified as promising candidates for catalyzing CO 2 electroreduction to CO, CH 4 , and CH 3 OH, respectively, with a substantially reduced overpotential.…”
Section: Introductionmentioning
confidence: 99%